Pengaruh Influencer Marketing dan Brand Image terhadap Keputusan Pembelian Produk Skincare Skintific (Studi Kasus pada Konsumen Sociolla di Kecamatan Medan Baru) - Fauziah Fauziah; Amrin Mulia Utama Nst (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to examine and analyze the partial and simultaneous effects of Influencer Marketing and Brand Image on Purchasing Decisions of Skintific skincare products among consumers of Sociolla in Medan Baru District. Increasing competition in the skincare industry and the relatively low level of consumer purchasing decisions toward Skintific products indicate uncertainty in consumer behavior, which encourages this study to identify the main factors influencing purchasing decisions. This research uses a quantitative approach with an associative research design. Data were collected through questionnaires distributed to respondents who are Sociolla consumers in Medan Baru District. The data analysis technique used is Multiple Linear Regression Analysis preceded by Validity Tests, Reliability Tests, and Classical Assumption Tests consisting of normality, multicollinearity, and heteroscedasticity tests. The results show that Influencer Marketing and Brand Image have a positive and significant effect on Purchasing Decisions both partially and simultaneously. Based on the t-test results, each independent variable has a significant effect on Purchasing Decisions with significance values below 0.05. Furthermore, the F-test results indicate that Influencer Marketing and Brand Image simultaneously have a positive and significant effect on Purchasing Decisions. The coefficient of determination test shows that Influencer Marketing and Brand Image variables explain the variation in Purchasing Decisions in a fairly strong category. The conclusion of this study emphasizes the importance of improving marketing strategies through the use of credible influencers and strengthening brand image in order to increase consumer trust and encourage purchasing decisions of Skintific products